Optimization of Protein Extraction from The Novel Oil Crop Field Cress Press Cake - Salim,Abdull-Wahidi Hamad; Huda,Luthfi Fathul (2025)
This study investigated the sustainable extraction of protein from field cress (Lepidium Cam-pestre) press cake, an underutilized by-product of oil extraction from a novel oilseed crop, which is currently being domesticated in Sweden. Field cress is recognized for its resilience in Nordic climates and its potential as a source of sustainable aviation fuel (SAF), yet the protein and fibre-rich cake generated during the oil extraction has historically been relegated to low-value uses such as animal feed or discarded as waste. The pH-shifting method was carried out to establish the baseline of field cress press cake protein extraction. The baseline of protein extraction only yielded approximately 3%. This result led to a further extraction using the enzyme-assisted protein extraction method. The enzyme-assisted protein extraction method was used to optimise the protein recovery yield. The enzymatic hydrolysis facilitated the disruption of the plant cell wall matrix and released the trapped protein. Among the five enzymes used, cellulase (Cellic® Ctec 3 HS) was identi-fied as the most effective enzyme, in which its relatively low dosage of 1.2 millilitres per extraction batch significantly improved the protein yield. The dosage not only enhanced the process efficiency but also reduced the operational cost and energy input, making the method suitable for industrial upscaling. The optimized protocol involved mixing the press cakes with water, enzymatic treatment, and a two-step pH adjustment-first to solubilize protein and then to precipitate and recover it. The extraction pH at 12.0 yielded higher values than lower pH, approximately 40%, while the precipitation pH at 5.0 led to a higher precipitation coefficient, around 80%. When tak-ing all steps into account, the highest protein recovery yield (39%) was achieved at alkali pH 12.0 and precipitation at pH 4.0. Beyond technical optimization, this study situates its work within the broader context of the global food system and climate change. With agriculture and food processing contributing substantially to greenhouse gas emissions, the valorisation of agricultural by-products like field cress press cake is essential for advancing circular bioeconomy principles and reducing food waste. Moreover, this study aligns with the UN Sustainable Development Goals for zero hunger and responsible production. The outcomes of this study demonstrate that field cress press cake can be efficiently convert-ed into functional protein ingredients. This study contributes to environmental stewardship and the diversification of protein sources for a growing global population by unlocking the potential of what was considered waste.
Keywords: Field cress press cake; oilseed crop; viscosity; protein extraction; enzymatic hydrolysis; cellulase; pH adjustment; protein yield; sustainable process; food engineering nutrition and food chemistry